ABUNDANCE, BIOMASS AND SPECIES OF EARTHWORM IN ECOSYSTEMS OF URBAN AREAS - Ressetti, Robinson Rolim (Scientia Agraria, 2006)
It is well established that earthworm population is strongly affected by soil management under agricultural areas and has been used as bioindicator of the soil quality. However, the urbanization process has been increased rapidly and may also provide great changes in the soil characteristics, but its impact on the earthworm population has been seldom studied. In that way, earthworm abundance, biomass and species were determined in different ecosystems at UFPR campus, located in Curitiba city Parana state. Five ecosystems were evaluated: disturbed native forest, manduirana (Senna macranthera) plantation, lawn, cultivated pasture and perennial pasture. The earthworm extraction was conducted on March 2003, using formaldehyde solution. The results indicated a large variation on population with 73, 44, 36, 23 and 17 ind.m-2 for perennial pasture, manduirana plantation, disturbed native forest, lawn and cultivated pasture, respectively. Difference on earthworm size among ecosystems provided biomass of 26.3, 12.9, 12.3, 11.7, and 6.7 g.m-2 for perennial pasture, cultivated pasture, disturbed native forest, lawn, and manduirana plantation, respectively. Three exotic species were found in all ecosystems [Metaphire californica, Amynthas gracilis (Megascolecidae) and Pontoscolex corethrurus (Glossoscolecidae)]. Thus, the earthworm population showed to be highly sensitive to the use of soil in urban condition.